THE EFFECT OF PRODUCT QUALITY TO THE LOYALTY OF TAHU TEMPE NUR CAHYO CONSUMERS IN BIAK PAPUA - Krismiyati, Krismiyati; Nurfadillah, Nurfadillah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Nur Cahyo is one of the industry players producing tahu and tempe in Biak Papua. The quality of the product that the product offered by the seller has an extra selling value that is not owned by the competitor's products. In Biak Numfor Regency, there are several entrepreneurs who open businesses in the field of tahu and tempe production, one of which is tahu and tempe Nur Cahyo production. Every month Nur Cahyo supplies ± 40 tons of soybeans. With the daily production of tempe as much as ± 200 pieces and also tahu. The research objective was to determine the influence of product quality on consumer loyalty to tahu and tempe Nur Cahyo in Biak Papua. This research uses the quantitative method. In this research the sample set is consumers who purchase tahu and tempe Nur Cahyo industry from 250 populations using the Slovin formula with a margin of error of 5%, the results are 154 in other words the sample from the research as many as 154. Sampling technique non-probability sampling. The sampling of respondents was done using purposive sampling technique, the sample criteria or data sources selected in the study were consumers or customers who purchased tahu and tempe Nur Cahyo in Biak Papua. From the decision-making criteria for the hypothesis, there is a significant positive effect between product quality and consumer loyalty as seen from the tcount 10.357 > from the ttable value 1.987. With a significant value of 0.000 < 0.05, then Ho is rejected and H1 is accepted, which means that there is a significant effect of the product quality variable (X) on the loyalty variable (Y). Research results Product quality variable (X) after hypothesis testing There is an influence between product quality on consumer loyalty of tahu and tempe Nur Cahyo industry. The magnitude of the influence of product quality on customer loyalty can be seen in the value of the coefficient of determination (R2) which has a value of 0.523 or 52.3%. Keywords: Product Quality, Loyalty, Customers, Tahu Tempe